Innovative strategies to enhance the sensory quality of dry fermented sausages containing lactic ingredients by the addition of exogenous enzymes. (July 2022) - Stollewerk, Katharina; Jofré, Anna; Comaposada, Josep; Guardia, M. Dolors; Arnau, Jacint; Kilcawley, Kieran
This study investigated the impact of the addition of exogenous enzymes (Accelerzyme CPG, Debitrase DBP20) or cellular preparations (FlavoGard), traditionally used in the cheese industry, to accelerate flavour development of dry fermented sausages with 6% of lactic derivatives content. Sausages were fermented to pH 5.0, dried for 32 days and vacuum packed stored under refrigeration for 60 days. Sausages were analysed for physicochemical parameters, technological microbiota and proteolysis after fermentation, drying/ripening and storage. Similar compositional results were obtained in all products (38-39% humidity in the final product; 38.2% fat and 40.7% protein as dry matter throughout the study). Debitrase application positively affected proteolysis by changing the free amino acid profile and increasing non-protein nitrogen and total free amino acids by 2.2 and 11.8-fold, respectively. Accelerzyme increased ripened cheese flavour and overall sensory quality from 5.1 to 5.8; Debitrase increased ripened cheese odour and flavour, bitterness, umami, adhesiveness, pastiness, and overall sensory quality from 5.0 to 5.9, and decreased acid and hardness. This study highlights the effects of adding some exogenous enzyme/bacterial preparations traditionally used in the cheese industry to enhance the flavour of dry fermented sausages with high content of lactic ingredients and increase its sensory quality.